"On Both Sides": Translingualism, Translation and Border-Crossing in Zinaida Lindén's Takakirves-Tokyo. Issue 2 (2nd July 2016) - Sorvari, Marja
ABSTRACT: This article examines the ways in which the Russian-Finnish-Swedish writer Zinaida Lindén discusses the question of language, identity and migration in her novel Takakirves-Tokyo (2007), written and published first in Swedish. The theoretical approach is framed by the concept of translingual literature, that is, literature written by writers in other language than their native one. In contrast to the Russian translingual writers in the USA, France or Germany, where the writer chooses the language of the majority, Lindén writes in the language of a minority in Finland, Swedish. This choice of language has important consequences for the representation of the translingual writer in the novel. Through writing fiction in Swedish, the writer as if becomes incorporated against her will to Finnish-Swedish literature. The novel's discussion of the translingual writer's situation reflects the difficulty of finding a place for her in disciplines connected to national histories, cultures and literatures. The article suggests that Lindén's novel cannot be read just as "Swedish" or "Russian": the translingual literary style implies simultaneous location "on both sides".